2000
DOI: 10.1038/sj.cgt.7700212
|View full text |Cite
|
Sign up to set email alerts
|

Transgene amplification and persistence after delivery of retroviral vector and packaging functions with E1/E4-deleted adenoviruses

Abstract: Adenovirus DNA is rapidly lost in actively dividing cells. In addition, first-generation (E1-defective) vectors trigger a strong cytotoxicity that impairs the duration of transgene expression. To solve these issues, we have developed a chimeric vector system that uses E1/E4 doubly defective adenoviruses for efficient production of infectious retroviral vectors. The retroviral vector sequences and packaging functions were split into two E1/E3/E4-deleted adenoviral vectors: the Moloney murine leukemia virus gag-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Initial studies of the co-transduction of adeno-retroviral hybrid vectors showed that transient retrovirus-producing cells can be successfully generated and that these could subsequently cause the transduction of neighboring cells [3,7]. Torrent et al [9] also reported a study with a chimeric vector system that resulted in 10-to 50-fold transgene amplification in vivo, although they did not examine the distribution of the transgene or the therapeutic efficacy of their system. In the study reported here, we have altered these hybrid adeno-retroviral vector systems so that the tumor-killing effect of adenovirus-mediated HSV-tk/GCV therapy in situ is enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies of the co-transduction of adeno-retroviral hybrid vectors showed that transient retrovirus-producing cells can be successfully generated and that these could subsequently cause the transduction of neighboring cells [3,7]. Torrent et al [9] also reported a study with a chimeric vector system that resulted in 10-to 50-fold transgene amplification in vivo, although they did not examine the distribution of the transgene or the therapeutic efficacy of their system. In the study reported here, we have altered these hybrid adeno-retroviral vector systems so that the tumor-killing effect of adenovirus-mediated HSV-tk/GCV therapy in situ is enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously described hybrid vector systems that use adenoviral vectors to deliver retroviral vector and packaging proteins into cells [3][4][5][6][7][8][9]. These systems benefit from the efficient gene transfer characteristics of adenoviral vectors as well as from the stable and long-term gene expression that is typical of retroviral vectors.…”
Section: Introductionmentioning
confidence: 99%